Impact of Neighbourhood Safety on Residential Rental Property Vacancy in Bida - Saidu, U. A.; Mohammed, J. K.; Nathaniel, S. (International Journal of Real Estate, 2025)
Safety of residence in an environment is a major priority and consideration by potential occupants of residential properties before making the decision to reside in a building or an environment. This study examined the impact of neighbourhoods’ safety on vacancy of residential rental properties in Bida, Nigeria. A quantitative approach was adopted with administration of questionnaire on residents of rental properties from three neighbourhood densities (high, medium and low) across the study area. The collected data were analysed descriptively and presented in frequency tables while relative importance index (RII) was used to rank the determinants of residential rental vacancy. Results revealed that high level of gang activities, burglary of homes alongside unsecured vacant properties are the most disturbing security concerns across the study area. Further analysis indicated that area 8 had the highest vacancy rate of 8.7% followed by Dokodza with 4.89% while FMC has the lowest vacancy rate of residential rental properties in the study area with 4.78%. Poor location, property condition and age alongside accessibility were the highest ranked determinants of vacancy rate of rental properties with RII values above 0.72. The regression analysis indicated that vacancy of rental property in Dokodza and Area 8 is significantly impacted by neighbourhood safety with p-value below 0.005 (.043 and .041 respectively) while neighbourhood security is not significant as a determinant of vacancy rate in FMC quarters (p-value = 0667). The study therefore concluded that, neighbourhood security has a significant impact on vacancy of residential rental property with other underlying factors peculiar to low density neighbourhoods. It was recommended that property owners and policy makers should prioritise routine surveillance and patrols alongside investment in advance security infrastructures to enhance safety and reduce vacancies.